Nursing students’ perception about the senses and meanings of nurses’ management work (Brazilian Journal of Health Research, 2020)
Introduction: Managerial function comprises nurse’s work process at different health care levels and aims at assuring the provision of high-quality and efficient care, which requires technical and scientific knowledge to be accomplished. Objectives: Investigating nursing students’ perception about the senses and meanings of nurse’ managerial work, as well as identifying nurses’ difficulty (ies) and/ or easiness in performing managerial work based on nursing students’ perception. Methods: Qualitative research conducted with ten nursing students, whose data were collected based on the semi-structured interview technique. Content Analysis Technique was used for data analysis. Results: Nurses’ managerial work is associated with work and health service organization, as well as with planning the provided services. Students have identified professional training, teamwork and dialogue as the easy parts of the managerial work development process. Challenges faced by nurses in associating care and managerial work, work overload, leadership relationship with the team and lack of material resources were mentioned as difficulties. Conclusion: The association between managerial and care work must be emphasized and built in professionals’ daily routine, since both are part of Brazilian nurses’ activities and validate such a profession.
Keywords: Health Service Management; Nurse; Health Care Delivery